The Incidence, Predisposing Factors, Complications and Outcome of Preeclampsia in Diabetic Pregnancy (BIRDEM Medical Journal, 2012)
Introduction: Preeclampsia is a serious complication of pregnancy and common cause of fetal and maternal morbidity as well as mortality worldwide. In diabetic women, the chance of preeclampsia is increased. The incidence of preeclampsia in diabetic pregnancy is approximately 10 to 15 percent, which is associated with poor glycaemic control. Aim: This study was carried out to find the predisposing factors related to preeclampsia and determine the complications of preeclampsia in diabetic pregnancy and also the impact of preeclampsia in infants born to diabetic mothers. Methods: This prospective study was carried out at the Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka. The Patient population consisted of 80 diabetic pregnant women who attended or admitted to BIRDEM hospital during the study period. The women were divided into groups: 50 pregnant diabetic women with preeclampsia were taken as case. 30 pregnant diabetic women without preeclampsia were taken as control. Diagnosis of preeclampsia was made on the basis of the criteria of the Committee on Terminology of the American College of Obstetrician and Gynecologist. Results: Preterm delivery (